Grade 4 reading comprehension achievement for isiZulu-speaking learners : comparing mother-tongue and English outcomes - Roux, Karen (University of Pretoria, 2025)
Dissertation (MEd (Assessment and Quality Assurance))--University of Pretoria, 2024.